128k views
5 votes
Help me, thank you!!!

Help me, thank you!!!-example-1

1 Answer

3 votes

Answer:

Explanation:

i don't understand this language but i think you want to simplify it.


(3x-3√(x) -3)/(x+√(x) -2) -(√(x) +1)/(√(x) +2) +(√(x) -2)/(1-√(x) ) \\=(3x-3√(x) -3)/(x+2√(x) -√(x) -2) -(√(x) +1)/(√(x) +2) -(√(x) -2)/(√(x) -1) \\=(3x-3√(x) -3)/(√(x) (√(x) +2)-1(√(x) +2)) -((√(x) +1)(√(x) -1)+(√(x) +2)(√(x) -2))/((√(x) +2)(√(x) -1)) \\=(3x-3√(x) -3)/((√(x) +2)(√(x) -1)) -((x-1)+(x-2))/((√(x) +2)(√(x) -1)) \\


=(3x-3√(x) -3-2x+3)/((√(x) +2)(√(x) -1)) \\=(x-3√(x) )/((√(x) +2)(√(x) -1))

User Derek Lewis
by
5.7k points